Efficacy of hydrotalcite Mg-Al membrane based on ghassoul and olive stone in the removal of polyphenols from olive mill wastewater - Safae Allaoui; Hamid Ziyat; Marwa Alaqarbeh; Fatima Boukhlifi; Najib Tijani; Mohammed Naciri Bennani (Arabian Journal of Chemistry, 2024)
The current study aims to fabricate a Hydrotalcite Mg-Al membrane (HT-Gh-OS3) based on Ghassoul and olive stone composite as a microfilter to remove of polyphenols from olive mill wastewater. Also, the results and efficiency of HT-Gh-OS3 membrane was compared with HT-Gh-AC3 membrane used in our previous study where Gh=Ghassoul, OS=olive stone, AC=activated carbon, number 3 relating to the percentage of AC or OS, and HT=Hydrotalcite type MgAlCO3. The hydrotalcite was deposited on the ceramic supports ‘Ghassoul’ and characterized by Fourier Transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and Scanning electron microscopy coupled with Energy-dispersive X-ray spectroscopy (SEM/EDX). The diluted OMW with water 40 %, 60 %, and 80 % contains 60 mg/L, 40 mg/L, and 30 mg/L concentrations of polyphenols respectively, which used in the filtration process by the new membrane. The results showed that the olive stone membrane has good porosity and reduced polyphenols by 74 % compared to 61 % by commercial activated carbon membrane. The macroporous structure of olive stones enhances the porosity of the support during sintering, resulting in a higher membrane porosity and better polyphenol reduction. The Hydrotalcite membrane based on the natural material (Ghassoul clay and olive stone) give a good retention of polyphenols of OMWW than the membrane with activated carbon.